2016
DOI: 10.3402/fnr.v60.32603
|View full text |Cite
|
Sign up to set email alerts
|

Food as a tool for learning in everyday activities at preschool – an exploratory study from Sweden

Abstract: BackgroundThere is a need for research both in relation to food education at preschools and in relation to how the individual teacher can handle and relate to the many different scientific facts and paradigms that are prevalent in relation to food, health, and a sustainable lifestyle.ObjectiveThe aim of this study was to explore the experiences and meanings that preschool teachers associate with involving food as a tool for learning in planned educational activities.DesignAn exploratory study was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
2
7
0
3
Order By: Relevance
“…Therefore, one benefit of sensory-based food education could be the enhancement of a positive atmosphere in children’s groups in relation to food. This is in line with a Swedish study ( 46 ) which noted that ECEC children learn from and with each other also in relation to food.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, one benefit of sensory-based food education could be the enhancement of a positive atmosphere in children’s groups in relation to food. This is in line with a Swedish study ( 46 ) which noted that ECEC children learn from and with each other also in relation to food.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has also stated the important role of the school as well as preschool to both form and impact children's food behaviour, aiming at reducing food neophobia and increase the willingness to try new food (see e.g., Part & Cho, 2016). However, earlier studies have also indicated the limited knowledge and experience of preschool teachers regarding food (Sepp, Abrahamsson, & Fjellström, 2006; Sepp & Höijer, 2016), which might impact the overall possibilities to talk about and experimenting around novel food together with the children. Therefore, future research needs to further focus on the role of the school and preschool in both understanding attitudes and promoting acceptance of sustainable food in general and novel food, including insects, in specific.…”
Section: Discussionmentioning
confidence: 99%
“…Studies centered on incorporating nutrition in the classroom have demonstrated increased levels of academic achievement, initiative, and core content knowledge (Berezowitz et al, 2015;Duffrin et al, 2010;Sepp & Höijer, 2016;Stage et al, 2018). Despite this evidence, the integration of content related to nutrition as a pedagogical approach is often perceived by teachers as a daunting task with multiple barriers such as lack of support, instructional time, and responsibility towards delivering nutrition education (O'Dea, 2016;Hall et al, 2016;Perikkou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that 97% of the teachers found nutrition education to be somewhat to very important in elementary classrooms, and 87% of teachers indicated that it was the responsibility of teachers together with students' parents to impart nutrition education to children (Perera et al, 2015). Teachers have also reported difficulty in integrating nutrition into lessons because of cost restraints and lack of administrative support (Metos, Sarnoff, & Jordan, 2018;Sepp & Höijer, 2016). This lack of support can mitigate teachers' motivation to incorporate nutrition into their classrooms and take on this extra-role behavior (Prelip et al, 2006).…”
Section: Extra-role Behavior and Supportmentioning
confidence: 99%